The Effect of Creative Writing Activities on the Story Writing Skill - Mehmet TEMİZKAN (Mustafa Kemal University, 2023)
The aim of this research is to determine the effect of creative writing activities on the skill of university students in writing story genre text. Unequaled control group model which is half experimental is used in this research. 1/A section (experimental group) of standard class and 1/B section (control group) of evening class from Turkish Language Teaching Department of Gazi Education Faculty of Gazi University constitute the sample of the research. 60 students participate in the research in total. The data obtained from the result of creative writing activities processed in 10 weeks are evaluated with regard to “The Scale of Story Writing Skill ”. It has been revealed that according to scale of story writing skill there is statistically a significant difference between the points [t(29) = -5,172; p≤,05 ] the students got from the post-test in the experimental and the control group. In other words, creative writing activities are more effective than traditional writing education in improving story writing skill. Besides, creative writing activities have a significant effect on content dimension [ t(29) = -3,668; p≤ ,05 ]; planning dimension [ t(29) =-3, 151; p≤ ,05 ]; characterization dimension [ t(29) = -5,666; p≤ ,05]; setting dimension [t(29) =-4,479; p≤ ,05 ] , and time dimension [ t(29) =-4,471; p≤ ,05 ] of story structure. According to these results, creative writing activities should be mentioned in Turkish courses and confidence in classroom should be taught in the relevant department of teacher training agencies and preservice teachers should be trained as qualified ones in terms of both practical and theoretical aspects of creative writing